PEMERIKSAAN PENGGABUNGAN GUGATAN GANTI KERUGIAN DALAM PERKARA PIDANA DI PENGADILAN NEGERI KELAS 1B BUKITTINGGI - Putri, Rianda Prima (Kopertis Wilayah X, 2018)
Basically, compensation is a civil case. However, once the criminal law law is applied, compensation can be made in conjunction with a criminal case. Although claims of merger compensation in a criminal case have been written in criminal law, this type of case is hardly found in court. This research proposes to answer 3 (three) problems related to the implementation of the merger claims for compensation (1) the conduct of examination of the merger claims for compensation in a criminal case in Class I Court of B Bukittinggi; (2) judges consideration in making decisions in cases where compensation is combined with a criminal case in Class I Court of B Bukittinggi; (3) obstacles in conducting examination of merger claims for compensation in a criminal case in Class I Court of B Bukittinggi. obstacles encountered in the implementation of the merger of the indemnification lawsuits in the criminal case at the IB Negeri Bukittinggi State Court are: a) Lack of public knowledge; b) have made a peace effort by replacing all losses suffered by the victim (material loss); c) Judges consideration of the economic level of the defendant who has been sued for damages by the plaintiff or victim; d) Plaintiff or victim must be able to prove the total loss he or she has suffered.